Roots of ‘BRS Princesa’ banana fertigated with humic substances and saponin-based plant extracts - Eugênio Ferreira Coelho; Diego Magalhães de Melo; Bruno Laecio da Silva Pereira; Djalma Barbosa dos Santos; Raul Castro Carriello Rosa (Acta Scientiarum. Agronomy, 2016)
This study aimed to evaluate the effects of fertigation with humic substances, with and without the addition of plant extracts, on the root system of the 'BRS Princesa' banana cultivar. The banana crop was cultivated at a spacing of 2.0 x 2.5 m and fertigated using a drip system in a dystrocohesive Yellow Latosol. The experimental design was randomized blocks, in a split-split-plot scheme with five replicates, for the following factors: humic substance doses and presence of a plant extract formulation. The treatments consisted of five doses of humic substances, based on a reference dose of 14.14 L ha-1 cycle-1, in the presence and absence of plant extract. The variable root length (cm) was subjected to variance analyses to evaluate the effect of the humic substances, either isolated or in interaction with plant extract and soil depth. The use of the plant extract increased the effect of the humic substance on root length but overshadowed its effect for the different doses of humic substance. Root length was not sensitive to increasing humic substance dose with plant extract for doses of up to 42.42 L ha-1at 0 – 0.40 m depth.